2020
DOI: 10.1029/2020ja028567
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐Lobe Reconnection and Horse‐Collar Auroras

Abstract: We propose a mechanism for the formation of the horse-collar auroral configuration during periods of strongly northward interplanetary magnetic field (IMF), invoking the action of dual-lobe reconnection (DLR). Auroral observations are provided by the Imager for Magnetopause-to-Aurora Global Exploration (IMAGE) satellite and spacecraft of the Defense Meteorological Satellite Program (DMSP). We also use ionospheric flow measurements from DMSP and polar maps of field-aligned currents (FACs) derived from the Activ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
93
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(119 citation statements)
references
References 81 publications
21
93
1
Order By: Relevance
“…Examples include the effects of changes in the IMF B Y component (Cowley, Morelli, & Lockwood, 1991;Lockwood, 1991) or transient and propagating filamentary field aligned currents in traveling convection vortices induced by solar wind dynamic pressure pulses (e.g., Lühr et al, 1996). In addition, prolonged northward IMF can lead to open flux collecting toward midnight, giving a more triangular open flux region LOCKWOOD AND MCWILLIAMS characteristic of the "horse-collar" pattern in global auroral images (Birn et al, 1991;Hones et al, 1989): it has been proposed that this is enhanced by lobe reconnection taking place in both the hemispheres which removes dayside open flux (Milan et al, 2020). Hence, the use of a circular open polar cap in Figures 2 and 3 is illustrative only.…”
Section: Transpolar Voltage Steady State and Non-steady-state Convectionmentioning
confidence: 99%
“…Examples include the effects of changes in the IMF B Y component (Cowley, Morelli, & Lockwood, 1991;Lockwood, 1991) or transient and propagating filamentary field aligned currents in traveling convection vortices induced by solar wind dynamic pressure pulses (e.g., Lühr et al, 1996). In addition, prolonged northward IMF can lead to open flux collecting toward midnight, giving a more triangular open flux region LOCKWOOD AND MCWILLIAMS characteristic of the "horse-collar" pattern in global auroral images (Birn et al, 1991;Hones et al, 1989): it has been proposed that this is enhanced by lobe reconnection taking place in both the hemispheres which removes dayside open flux (Milan et al, 2020). Hence, the use of a circular open polar cap in Figures 2 and 3 is illustrative only.…”
Section: Transpolar Voltage Steady State and Non-steady-state Convectionmentioning
confidence: 99%
“…(2008) during IMF B y dominated periods in the Cluster EDI data, without mapping the measurements to the ionosphere. This behavior is expected from the lobe reconnection process, and is often referred to as stirring of lobe flux (e.g., Milan et al., 2020; Reiff & Burch, 1985). In the following discussion we interpret our quantified measure of plasma circulation within the polar cap, Φ lobe , as an estimate of an average lobe reconnection rate associated with the data selection conditions.…”
Section: Discussionmentioning
confidence: 95%
“…Analysis of the R 1 distribution by Rogers et al. (2020) showed that these peaks near noon occur predominantly under northward IMF conditions during the summer months (i.e., under conditions of greatest dipole tilt angle), suggesting a possible relation to impulsive field line reconnection between the IMF and an “overdraped” tail lobe (Crooker, 1992; Milan et al., 2017, 2020; Wang et al., 2008; Watanabe et al., 2005). The MLT distribution of occurrence probability at dayside cusp latitudes does not match the distributions of MIEs observed by Lanzerotti et al.…”
Section: Latitude Mlt and Seasonal Distribution Of Large Rn And Sn On...mentioning
confidence: 99%
“…(Note that the timestamps and MLTs associated with each cluster peak of / h E dB dt refers to the end of the n-minute period in question (from Equations 2 and 4) but this is not sufficient to account for the apparent shift of the maximum toward postnoon.) Analysis of the R 1 distribution by Rogers et al (2020) showed that these peaks near noon occur predominantly under northward IMF conditions during the summer months (i.e., under conditions of greatest dipole tilt angle), suggesting a possible relation to impulsive field line reconnection between the IMF and an "overdraped" tail lobe (Crooker, 1992;Milan et al, 2017Milan et al, , 2020Wang et al, 2008;Watanabe et al, 2005).…”
mentioning
confidence: 99%